Estudio de adaptación de siete Pastos y Tres Mezclas Forrajeras con la utilización de Lactofermento en el Sector Salache Bajo Universidad Técnica de Cotopaxi, Parroquia Eloy Alfaro, Cantón Latacunga, Provincia de Cotopaxi en el periodo 2018-2019 - Curicho Pazuña, Jeaneth Paulina (2019)
The present investigation was carried out in the Lower of Salache Sector, Parish Eloy Alfaro, CantonLatacunga, Province of Cotopaxi, Technical University of Cotopaxi, Faculty of Agricultural Sciences and Natural Resources. In order to study the adaptation of seven kinds of grass and three forage mixtures with the use of fortified lactoferrin. The methodology to be followed is an experimental design of divided plots (A x B), twenty treatments y three repetitionsgiving a total of 60 experimental units; With the statistical Tukey analysis test at 5%, the best treatment was detremined according to the variables to be evaluated, average height of the plant, percentage of coverage and proximal bromatological analysis. Having as a result the best averages in height at 43 and 50 days with averages of 31.93 cm and 38.4 cm without the aplication of Lactoferment (L0) having the T4 (Ryegrass) with a range A. In percentage of plant cover at 57 days we can see who had the highest percentage was the T2 (Red clover) with the application of (L1) with an average of 87,3 with a range A, followed by the T3 (With clover) with the aplication (L1)with an average of 82.33% with a range of AB, Then the aplication if I influence the treatments. The results obtained in the bromatological analysis are the following: humidity is T5 (Chicory) with an average of 87.57%, with a range A, dry matter T1 (bluegrass) 19.75% with a range A, protein T2 (Red clover) with an average of 20.52% with a range of A, raw fiber T4 (Ryegrass) with an average of 26.25% with a range of A, fat T9 (oat-vetch) with an average of 2.25% with a range of A, ash T1 (bluegrass) with an average of 12.16%. with a range of A, organic matter T6 (tare) with an average of 90.35% .with a range of A, ELN T9 (oat-vetch) with an average of 56.34%. with a range of A.